Analysis of Students Concept Mastery on Forces on Objects in Static Fluid with Interactive Demonstration Learning - Widya Rohmawati; Sutopo Sutopo; Bruce Waldrip; Kurnaz , Mehmet Altan; Sharona T. Levy (Tinta Emas Publisher, 2024)
This study aims to analyze the improvement of concept mastery of grade XI students about forces on objects in static fluid after being given interactive demonstration learning. The research method used is mixed method-embedded experimental design with one-group pretest-posttest design. The research subjects were students of class 4KJ SMK Universiti Malaysia and class H3 SMA Negeri 5 Malang. The instruments used were concept mastery test items regarding forces on objects in static fluid in the form of reasoned multiple choice questions, observation sheets, and interview guidelines. The results showed that the calculation of the d-effect size value of the learning applied to students of SMK Taman Universiti and SMAN 5 Malang was 4.50 and 4.28. The value of increasing student learning outcomes through the calculation of the average normalized gain is 0.88 and 0.83. The results also show that students can integrate Newton's laws in analyzing the problems of Archimedes' law after the learning is applied. For future research, similar learning can be applied to improve students concept mastery on other physics materials.